Defender Fantasía: Hacia un modelo de crítica cultural feminista - Garzón Martínez, María Teresa (2018)
The present article aims to reflect on the elements that can constitute a model of feminist cultural criticism, thought from the intersection between the field of feminist studies and critical cultural studies, with the aim of supporting the discussion about the “turnaround cultural” of feminism in Latin America. For this, classical texts of the aforementioned fields are visited to give a historical and epistemological meaning to the proposal and a narrative and political commitment is made by an exercise of “fabulation”, in which a metaphor is made of what it means to “make the culture “, from feminist positions, through the novel The Endless History (1979), by Michael Ende, arguing that the defense of Fantasía is equivalent to providing us with other frames of intelligibility, of other paradigms of thought and action, that address address the question of power and commit to projects of social transformation, in specific contexts.